Low rectal cancer: current approach based on magnetic resonance imaging - Valadão, Marcus; Câmara, Eduardo R.Z.; Araújo, Rodrigo; Jesus, José Paulo; Linhares, Eduardo; Carrada, Claudia (Brazilian Journal of Oncology, 2017)
The complex anatomy surrounding lower rectal cancer, as well as its aggressive biological behavior, creates surgical challenges. Furthermore, patients with lower rectal cancer have a poorer prognosis, compared to tumors in the middle and upper rectum. Thus, it is essential to adopt new strategies to optimize the results of surgical treatment. Magnetic resonance imaging has become a crucial tool for successfully selecting and completing surgery, as it provides a high anatomical resolution and the ability to define the tumor’s relationship with the sphincter complex. New surgical techniques based on magnetic resonance imaging can also improve patients’ oncological and functional outcomes. This review examines the modern approach to treating lower rectal cancer, and aims to simplify the complex decisions that surgery currently requires. The PubMed database was searched using the terms “lower rectal cancer”, “colorectal surgery”, and “magnetic resonance imaging”. Milestone reports from recent years have been addressed in this review.
Keywords: Rectal neoplasms/surgery; Colorectal surgery; Colorectal neoplasms; Magnetic resonance imaging